2019
DOI: 10.1088/1361-6560/ab2b72
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparison of proton CT and dual energy x-ray CT for relative stopping power estimation in proton therapy

Abstract: Proton computed tomography (pCT) has been proposed as an alternative to X-ray computed tomography (CT) for acquiring relative to water stopping power (RSP) maps used for proton treatment planning dose calculations. In parallel, it has been shown that dual energy X-ray CT (DECT) improves RSP accuracy when compared to conventional single energy X-ray CT. This study aimed at directly comparing the RSP accuracy of both modalities using phantoms scanned at an advanced prototype pCT scanner and a state-of-the-art DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
106
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(128 citation statements)
references
References 45 publications
(59 reference statements)
16
106
1
Order By: Relevance
“…Details about the modeling of physics processes can be found in literature, where the platform was validated for its fidelity in terms of RSP. 19,35 A previous study 34 improved the platform for reproducing variance levels of experimental scans. With respect to that work, the beam model was modified, and is described below.…”
Section: A Simulation Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Details about the modeling of physics processes can be found in literature, where the platform was validated for its fidelity in terms of RSP. 19,35 A previous study 34 improved the platform for reproducing variance levels of experimental scans. With respect to that work, the beam model was modified, and is described below.…”
Section: A Simulation Frameworkmentioning
confidence: 99%
“…RSP errors were comparable for modulated and un-modulated scans, and all below 1%, which is within the magnitude expected from literature. 12,19,35 Imaging doses in fluence-modulated scans showed local increases and doses partially spilled out of the ROI. This may have impaired results in this study and could be caused by the fact that optimization was exclusively performed with a variance objective.…”
Section: C Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental and simulation studies of the Phase-II pCT scanner [113,107,110,59] note the presence of artifacts in the RSP image. In Dedes et al [59], artifacts of up to 2 % in RSP were reported.…”
Section: Pct Image Artifactsmentioning
confidence: 99%
“…Many pCT systems have been proposed and developed in the past 20 years [15,16] achieving promising results for RSP accuracy and spatial resolution with both Monte Carlo (MC) simulated and experimental setups [17][18][19][20]. Lately, the RSP accuracy of pCT was proven to be well below 1% and performs better than modern techniques such as dual energy CT scans [21,22]. Additionally, pCT has shown reduced noise level and lower dose deposition on the patient with respect to conventional X-ray CT [23,24].…”
Section: Introductionmentioning
confidence: 99%